Критерії, показники та рівні сформованості професійно-прикладної фізичної підготовленості інженерів-механіків авіаційної галузі - Фотинюк, Володимир Григорович (НТУ "ХПІ", 2012)
This paper paid attention to the analysis of criteria and indicators, which can diagnose the level of professional-applied physical training of the future engineers of the airline industry. The content of high, medium and low levels of readiness.
Keywords: критерії; показники; рівні; професійно-прикладна фізична підготовка; інженери авіаційної галузі